Outcomes and Factors in Cerebral Infarction Treated by Decompressive Craniectomy - Sookprome, Sakol (Journal of Health Science of Thailand, 2017)
The objective of this analytic study was to investigate the outcome of patients suffering fromischemic strokes who were treated by decompressive craniectomy (DC) and factors associated withthe unfavorable outcome. Data was conducted to investigate patients suffering from Middle cere-bral artery (MCA) infarction who were treated with DC in Pranangklao hospital between January1,2007 and December 31, 2010. The medical records were reviewed and data collection age, sex,history of hypertension (HT), diabetes mellitus (DM), atrial fibrillation (AF), side of hemisphericinfarction, preoperative Glasgow coma scale (GCS), pupil asymmetry, midline shift and Glasgowoutcome scale (GOS). Fourteen patients were included in the present study. The overall mortalitywas 57.2 percent. There were high mortality in older age, lower preoperative GCS (3-6) and mid-line shift. Patients with lower GCS tended to have high risk of death after the operation. In summary, preoperative GCS is a potential factor of survival in patients suffering from MCAinfarction treated by decompressive craniectomy